Implikasi Pelanggaran Kode Etik Advokat Terhadap Kepercayaan Publik (Studi Kasus: Desrizal Chaniago) - Mussa’ad, Amirah Achmad; Mubarani, Ananta Siti (Media Hukum Indonesia (MHI), 2025)
One aspect highlighted by ethics and morals regarding a person's behavior is in the field of expertise called the profession. Advocates, judges, prosecutors and various other types of legal professions play a role in regulating and maintaining justice and order in society. However, it cannot be denied that sometimes violations of the code of ethics can lead to a negative view of legal professionals. One example is Desrizal, a lawyer who beat a judge, when the judge was reading the verdict in a case at the Central Jakarta District Court. This study uses a normative juridical approach which is then analyzed in the case and linked to laws and regulations which are then presented in the form of narrative text through descriptive specifications with qualitative normative analysis. Some people may feel that the legal system is unfair or ineffective in resolving their problems. This can reduce public trust in the legal profession and result in dissatisfaction with the existing legal system. The impact of the legal profession on society can also be seen in terms of inconsistent law enforcement. The purpose of this study discusses the effect of violations of the code of ethics by lawyers on the level of public trust in the legal profession in Indonesia and emphasizes the significance of ethical standards in maintaining the integrity of the justice system and building a relationship of trust between lawyers and the public.